Tata Kelola Wisata Pulau Gili Iyang: Perspektif Community Based Tourism - Moh. Musleh (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2023)
Sumenep Regency has many diverse tourism potentials, a very prominent tourist destination in Sumenep Regency is island tourism. Gili Iyang Island is also known as â€œOxygen Islandâ€, because it has natural tourism potential and high oxygen content potential (above 20% normal parks) compared to other regions in Indonesia (LAPAN). Gili I Island Tourism Development which requires community accessibility by playing an active and systematic role, the role of the community in understanding the management and utilization of tourism potential is very important in developing tourism in the region. Tourism management will be optimal if it is community-based. This study focuses on Tourism Governance of Gili Iyang Island: Community Based Tourist Perspective, by analyzing the level of participation of local communities on Gili Iyang Island in exploiting and developing tourism potential on Gili Iyang Island. Qualitative methods are used in this research method, and data collection techniques are in-depth interviews. Community Based Tourism theory Suansri (2003) is used in data analysis, with five principles of approach namely: (1) economic principles, (2) social principles, (3) cultural principles, (4) environmental principles and (5) political principles. The results of the study show that Tata managing tourism on Gili Iyang Island has been going well, as evidenced by the role of Pokdarwis in being able to create jobs in the tourism sector, increasing tourist visits to Gili Iyang Island. Environmental conservationists and the community can participate in tourism management, by becoming part of the Pokdarwis members.